Antimetastatic Activity of Apoptolidin A by Upregulation of N-Myc Downstream-Regulated Gene 1 Expression in Human Colorectal Cancer Cells - Kay Zin Kyaw; Jiyoon Park; Seung Ho Oh; Ji Yun Lee; Eun Seo Bae; Hyen Joo Park; Dong-Chan Oh; Sang Kook Lee (MDPI AG, 2023)
Colorectal cancer (CRC) is one of the most prevalent tumors with high metastatic potential; consequently, finding new drug candidates that suppress tumor metastasis is essential. Apoptolidin A is a macrocyclic lactone produced by Amycolatopsis sp. DW02G. It exhibits significant cytotoxicity against several cancer cell lines, but its effects on CRC cells remain unknown. Therefore, the present study investigated the antiproliferative and antimetastatic activities of apoptolidin A and its underlying molecular mechanisms in CRC cells. Apoptolidin A effectively inhibited CRC cell growth and colony formation. The induction of G0/G1 phase cell cycle arrest was associated with the downregulation of cyclin D1 and CDK4/6 expression. Long-term exposure to apoptolidin A also induced apoptosis as confirmed by the downregulation and upregulation of Bcl-2 and Bax expression, respectively. Moreover, apoptolidin A effectively upregulated the suppressed expression of N-Myc downstream-regulated gene 1 (NDRG1), a tumor suppressor gene, in a concentration-dependent manner in CRC cells. The antimetastatic potential of apoptolidin A was also correlated with the expression of epithelial-mesenchymal transition (EMT) biomarkers, including the upregulation of E-cadherin and downregulation of N-cadherin, vimentin, snail, and MMP9 in CRC cells. These findings suggest that apoptolidin A exerts antiproliferative and antimetastatic activities by regulating the NDRG1-activated EMT pathway in CRC cells.